Connotative Meaning of Olivia Rodrigo’s Selected Song Lyrics - Syafitri, Syafitri; Jufrizal, Jufrizal (Universitas Negeri Padang, 2024)
This research was conducted to analyze the connotative meaning of Olivia Rodrigo's song lyrics. The objectives of this research are (1) to identify the connotative meaning of Olivia Rodrigo's song lyrics, (2) to identify the connotative types in Olivia Rodrigo's song lyrics. This research uses the theory of Abdul Chaer which states that connotative meaning can be divided into two kinds, namely positive connotative (the word snoring) and negative connotative (the word growling). The researcher used a qualitative approach in analyzing the data. The data of this research are the songs by Olivia Rodrigo in the album Sour. five songs were selected: